CALCULATION OF THE MEASURING UNIT OF IN-MODEL TENSOMETRIC WEIGHTS IN THE MATNSAD ENVIRONMENT - Зінченко, В. П.; Зінченко, Н. П.; Муха, І. П. (Proceedings of National Aviation University (archive), 2021)
The technique and algorithm of the optimized calculation on durability and sensitivity of a beech for measurement of sieves of frontal resistance and a technique and algorithm of check calculations of the measuring block of ready tensometric scales on the set geometrical sizes and loading in the MATNSAD environment are offered.